THE EXISTENCE OF MORALITY AND RELIGION ABOUT EDUCATION IN COVID 19 ERA - Aminah, Siti (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2020)
Education is the important element in building human resource in nation development. This study aims to reveals the existence of morality and religion in education progress in covid 19 era. Through education, perhaps the students didn’t have science-technology only, but also science-religion (developing children be a good character and attitude). The qualitative analysis means to illustrate, explain, compare, and describe about moral and religion as the important thing in the education development. The result of study showed that the nation development exist about balance between morality and religion in education especially developing physical and spiritual based on national development purpose. Both are important, therefore if there is imbalance, impact in disorientation of national education development.